Terapi Seni bagi Anak Autis - Shirly Nathania Suhanjoyo; Stella Sondang (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Special needs children are children who need special treatment due to disorder on physical and psychological growth functions. One example of this disorder is autism. Autism is a disorder that includes cognitive, emotional, behavioral and social areas. In fact, children with autism have potential that is often overlooked. Art can help deal with this problem by applying various techniques of art therapy such as cutting, sticking and painting with a variety of media materials, textures, colors and shapes. Autistic children will get a pleasant and calming experience and other positive benefits. The creativity program for autistic children under the Percik Insani Foundation is in the form of art training that focuses on exploration and expression of every autistic child in the hope of improving fine motor function, creativity, self-potential and self-confidence that can help children to grow better and live more independently.